EFFECTS OF DIFFERENT RESTING INTERVALS PROGRAM ON REPEATED SPRINT ABILITY IN FEMALE FOOTBALL PLAYERS - Chor. Charoenying, Sukanya; Srihirun, Kanang (Journal of Sports Science and Health, 2021)
Purpose: The purpose of this study was to determine the effect of repeated sprint training programs with three different running to rest ratiosd (1:1, 1:2, and 1:3) on repeated sprint ability in female football Thai league players. Methods: Thirty-six female professional football players, aged between 18-24 years,were divided into 3 groups (12 persons per group). Each group was trained to run repeatedly with 3 different running to rest ratio of 1:1, 1:2 or 1:3. All groups trained twice a week for 6 weeks. The physiological parameters, repeated sprint ability and short-distance sprint time were measured before and after training. Data were analyzed using One-way ANOVA. The significant was set at <.05. Results: 1. After 6 weeks of training, the repeated sprint ability, the total repeated sprint time, the best sprint time, the average time of repeated sprint runs, and the percentage decrement score of were significantly decreased (p<.05) after training, only in 1:1 running to rest ratio group. However the running time of the sprint distance at 10 m, 20 m. and 40 m. were similarly decreased after training in all three groups (p<.05). 2. Comparing between groups, it was found that the total repeated sprint time, the best sprint time, the average time of repeated sprint runs, and the running time of the sprint distance at 10 meters of 1:1 running to rest ratio were lower after training than that of other groups (p<.05). Conclusion: Repeated sprint training program with three different recovery duration have beneficial effects on repeated sprint ability and short distance sprint duration in female football players, with the 1:1 running to rest ratio is the most effective in developing such skills.